An insecticide formulation of terpene ketones against Sitophilus zeamais and its incorporation into low density polyethylene films. (August 2017) - Herrera, Jimena M.; Goñi, María L.; Gañan, Nicolás A.; Zygadlo, Julio A.
Abstract: The use of active natural compounds derived from plants appears as an interesting alternative for pest control in stored products. In this study, the fumigant toxicity of several terpene ketones against maize weevil (Sitophilus zeamais) adults was assessed, and the effect of their combination with piperonyl butoxide (PBO), a cytochrome P450 inhibitor commonly used as synergistic agent, was investigated. A mixture of the most active ketones ( R -(+)-pulegone and thymoquinone) was then tested on S. zeamais, and finally this mixture was incorporated into low density polyethylene (LDPE) films by supercritical CO2 impregnation, in order to study the fumigant toxicity of this formulation against S. zeamais under laboratory conditions, as well as the release profile of the active ketones. PBO showed antagonistic effects in combination with terpene ketones, decreasing the toxicity of the individual compounds and therefore increasing their lethal concentrations. The mixture of ketones showed a lower lethal concentration (LC50 value of 7.12 μL/L air) than the individual compounds, thus indicating a synergistic effect between them. Finally, the impregnated films revealed high toxicity values (up to 95% mortality), and maintained a moderate level of activity even after 8 days of exposure. In conclusion, the mixture of these active terpene ketones incorporated into a polyethylene film, material commonly used for hermetic storage of maize grains, could be applied as a potential technology against insect pests. Highlights: The insecticidal activity of five terpene ketones was tested against S. zeamais in fumigant assays. R -(+)-pulegone and thymoquinone were the most active ketones and showed synergistic effects. Ketones were incorporated into LDPE films by supercritical CO2 impregnation. Fumigant toxicity of impregnated films was confirmed by in vitro tests.